2017
DOI: 10.1021/jacs.7b05214
|View full text |Cite
|
Sign up to set email alerts
|

Directed β C–H Amination of Alcohols via Radical Relay Chaperones

Abstract: A radical-mediated strategy for β C–H amination of alcohols has been developed. This approach employs a radical relay chaperone, which serves as a traceless director that facilitates selective C–H functionalization via 1,5-hydrogen atom transfer (HAT) and enables net incorporation of ammonia at the β carbon of alcohols. The chaperones presented herein enable direct access to imidate radicals, allowing their first use for H atom abstraction. A streamlined protocol enables rapid conversion of alcohols to their β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(63 citation statements)
references
References 48 publications
0
63
0
Order By: Relevance
“…Recently, Nagib et al reported interesting methods for the preparation of β‐amino alcohols through the reactions of (trichloromethyl)imidates prepared from alcohols and trichloroacetonitrile, with NaI and PhI(OAc) 2 under visible‐light irradiation, via the formation of iminyl radicals, their 1,5‐H shift, their cyclization to form oxazolines, and their hydrolysis , [8a] and the preparation of γ‐functionalized β‐amino alcohols from alcohols through the reactions of (trichloromethyl)imidates with NaI and PhI(OAc) 2 under visible light irradiation via the formation of amidyl radicals, their 1,5‐H shift, formation of olefinic group, iodocyclization, and their hydrolysis. [8b] He et al also reported the preparation of β‐amino alcohols from (trichloromethyl)imidates, and 2‐aryloxazolines from arylimidates with NIS or with NIS and Ag 2 O at 110 °C. [8c]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Nagib et al reported interesting methods for the preparation of β‐amino alcohols through the reactions of (trichloromethyl)imidates prepared from alcohols and trichloroacetonitrile, with NaI and PhI(OAc) 2 under visible‐light irradiation, via the formation of iminyl radicals, their 1,5‐H shift, their cyclization to form oxazolines, and their hydrolysis , [8a] and the preparation of γ‐functionalized β‐amino alcohols from alcohols through the reactions of (trichloromethyl)imidates with NaI and PhI(OAc) 2 under visible light irradiation via the formation of amidyl radicals, their 1,5‐H shift, formation of olefinic group, iodocyclization, and their hydrolysis. [8b] He et al also reported the preparation of β‐amino alcohols from (trichloromethyl)imidates, and 2‐aryloxazolines from arylimidates with NIS or with NIS and Ag 2 O at 110 °C. [8c]…”
Section: Introductionmentioning
confidence: 99%
“…[8b] He et al also reported the preparation of β‐amino alcohols from (trichloromethyl)imidates, and 2‐aryloxazolines from arylimidates with NIS or with NIS and Ag 2 O at 110 °C. [8c]…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen-centered radicals have drawn agreat deal of interest in recent years,l argely driven by photochemical innovation. [24,25] Prominent alternatives to amine radical cations include amidyl or imidyl radicals arising from oxidation of N À Hbonds [26,27] via proton-coupled electron transfer (PCET) [28] or from NÀXb onds via homolysis, [29][30][31] reduction, [32] or even oxidation [33] by employing a-aminoxy carboxylic acid auxiliaries popularized by the groups of Leonori [34,35] and Studer. [36,37] Alternatively,i tw as hypothesized that initiation of our desired fragmentation-cyclization sequence could be accomplished not from a discrete N-centered radical but a temporaneous N-centered radical.…”
Section: Introductionmentioning
confidence: 99%
“…Circumventing this limitation would require another means of accessing open-shell character at nitrogen (see Figure 1B). [24,25] Prominent alternatives to amine radical cations include amidyl or imidyl radicals arising from oxidation of N À Hbonds [26,27] via proton-coupled electron transfer (PCET) [28] or from NÀXb onds via homolysis, [29][30][31] reduction, [32] or even oxidation [33] by employing a-aminoxy carboxylic acid auxiliaries popularized by the groups of Leonori [34,35] and Studer. [24,25] Prominent alternatives to amine radical cations include amidyl or imidyl radicals arising from oxidation of N À Hbonds [26,27] via proton-coupled electron transfer (PCET) [28] or from NÀXb onds via homolysis, [29][30][31] reduction, [32] or even oxidation [33] by employing a-aminoxy carboxylic acid auxiliaries popularized by the groups of Leonori [34,35] and Studer.…”
Section: Introductionmentioning
confidence: 99%